2015
DOI: 10.1007/s10616-014-9839-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the in vitro cytotoxicity and in vivo anti-tumor activity of the alcoholic stem bark extract/fractions of Mimusops elengi Linn.

Abstract: Various parts of Mimusops elengi Linn. (Sapotaceae) have been used widely in traditional Indian medicine for the treatment of pain, inflammation and wounds. The study was conducted to explore the use of stem bark of M. elengi on pharmacological grounds and to evaluate the scientific basis of cytotoxic and anti-tumor activity. Extract/fractions were prepared and in vitro cytotoxicity was assessed using SRB assay. Most effective fractions were subjected to fluorescence microscopy based acridine orange/ethidium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
4
11
0
Order By: Relevance
“…Therefore, we observed that the combinatorial treatments of DOX with CQ and/or TIC increased MST (25~30 days), ILS% (60~90%) of MCF-7 tumor inoculated mammary mice when compared with untreated mice than either compared with control or dox treated groups ( Figure 2II-C). This is consistent with a study that reported the combinatorial treatments to be more effective as a significant reduction in tumor size with a prolonged life span, which was a significant criterion in determining the anticancer compound's effectiveness [35].…”
Section: Cytotoxic and Synergistically Effect Of Dox Cq And Tic By supporting
confidence: 91%
“…Therefore, we observed that the combinatorial treatments of DOX with CQ and/or TIC increased MST (25~30 days), ILS% (60~90%) of MCF-7 tumor inoculated mammary mice when compared with untreated mice than either compared with control or dox treated groups ( Figure 2II-C). This is consistent with a study that reported the combinatorial treatments to be more effective as a significant reduction in tumor size with a prolonged life span, which was a significant criterion in determining the anticancer compound's effectiveness [35].…”
Section: Cytotoxic and Synergistically Effect Of Dox Cq And Tic By supporting
confidence: 91%
“…Toxicological studies are usually done to predict the potential toxicity of the drug during drug development [ 49 ]. Toxicological evaluation of the combination of CP 404 and chlorambucil was carried out using mouse peritoneal cells as this combination showed the highest antiproliferative effects on Jurkat T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cytotoxicity is generally used to predict potential toxicity using cultured cells that may be normal or transformed cells such as mouse peritoneal cells [ 41 ]. The test typically involves short-term exposure of cultured cells to test compounds to identify how the compound may affect basal or specialised cell functions, before performing toxicological studies in whole organisms.…”
Section: Discussionmentioning
confidence: 99%